PROBLEMS OF MODERN COMPUTER ETHICS - Farrukh Usmonov (American Journals Publishing, 2022)
In this article highlights of problems modern computer ethics and the principles of solving ethical problems in the field of computer ethics are revealed, the general features of the new ethics of modern society are determined.
Keywords: information technology, computer ethics, information security, communication, virtual life.